In Home we trust. An ethnographic study of mental health and the use of traditional medicine in a North Norwegian community - Kiil, Mona Anita (UiT The Arctic University of Norway, 2019)
Traditional healing practices used when faced with illness or crisis, exist in many North Norwegian communities. Northern Troms has a historical multi-ethnicity of Sami, Kven and Norwegian. The notion of culture appears ambivalent and ambiguous, particularly concerning the Sami identity, but cultural diversity is nevertheless manifested through the use of traditional healing practices such as reading. Participants had all been diagnosed with depression and anxiety disorders and were users of the outpatient mental health care clinic for Northern Troms. In addition, conventional therapists at the clinic, traditional healers and complementary and alternative practitioners participated. Findings revealed embodied dynamics of belonging and trust. As users of traditional healing practices, the participants experienced a significant sense of vulnerability in their encounter with the conventional mental health care. Lack of trust in regard to how their traditional and religious practices are being understood were expressed. Fear of misdiagnosis should they communicate their world-view and personal treatment philosophies was one issue. Furthermore, the participants` stories give an understanding of nerves as an embodied idiom of distress in the region. Nerves appear closely connected to people`s experiences from the assimilation process and the expulsion from their homes during World War II. The continuous concealment which is surrounding these events interplays and has created trauma but also insights for the people in Northern Troms; through nerves identities are being negotiated. The participants are experienced navigators between the different cultural and medical systems available. Rupture of the traditional healing practices has the element of an increasing combination with CAM modalities. However, the distinction between traditional healing and CAM is still valid as it includes a navigation of competency and intentions of practitioners based on values and knowledge related to traditional healing.